2021
DOI: 10.19181/snsp.2021.9.4.8619
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Lifestyles and living Conditions of the Rural Population of the Russian Central Federal District as a Factor in the Dynamics of Human Capital

Abstract: The article raises the issue of the dynamics of human capital of rural Russia of the Central Federal District with the example of the Yaroslavl area in conditions of depopulation and growth of return migration. On the basis of the results of the empirical research, using the methods of in-depth interviews and the search survey according to the structured questionnaire, the author examines the way of life and living conditions of the rural population from the perspective of the past, present and future. The art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…A lot of studies of the quality of life and issues of rural areas can be found in Russian scientific literature. These studies are different: from those concerning separate settlements or municipal districts to those involving several regions [18][19]. Despite big differences in scales of the studies, geographical location of the analyzed rural areas, the applied method for determining quality of life, all those studies basically reveal the same set of quality of life issues typical for the rural areas.…”
Section: Resultsmentioning
confidence: 99%
“…A lot of studies of the quality of life and issues of rural areas can be found in Russian scientific literature. These studies are different: from those concerning separate settlements or municipal districts to those involving several regions [18][19]. Despite big differences in scales of the studies, geographical location of the analyzed rural areas, the applied method for determining quality of life, all those studies basically reveal the same set of quality of life issues typical for the rural areas.…”
Section: Resultsmentioning
confidence: 99%